Experiences in International Cooperation in Teaching - Welzer, T.; Družovec, M.; Hölbl, M.; Venuti, M. Z. (Elektronika ir Elektrotechnika, 2010)
International cooperation either in research or teaching is very important already for a vile. In research most of international cooperation is based either on bilateral agreements, either on different international projects and cooperation. Seems that researchers have been earlier involved in international exchange of knowledge and experiences as teachers. In the paper, we will present the experiences with international cooperation in teaching gained when teachers have been involved in mobility programs like Erasmus, transcontinental cooperation or they have taken part in distance and e-learning where the cooperation with international participants (teachers and students) is also possible.